The Role of Aqidah Akhlak Teachers in Preventing the Negative Impact of Social Media on Students at MTs Nurul Iman Pomalaa - Wahyuddin Kanna; Muh. Iqbal; Muhammad Asra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The rapid development of information and communication technology has brought major changes to people's lives, including the use of social media among students. Social media provides various benefits, but can also have negative impacts if not used wisely. Therefore, the role of teachers is very important in guiding students to be able to use social media positively and responsibly. This study aims to analyze the learning process of Aqidah Akhlak, identify the negative impacts of social media use, and examine the role of Aqidah Akhlak teachers in preventing these negative impacts on students at MTs Nurul Iman Pomalaa. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation with research subjects: the principal, Aqidah Akhlak teachers, and students. Data were analyzed through the stages of data reduction, data presentation, and conclusion. The results of the study indicate that Aqidah Akhlak learning at MTs Nurul Iman Pomalaa has been implemented well through various methods that emphasize the instillation of moral and religious values. The negative impacts of social media identified include a decreased interest in learning, excessive time spent on social media, and the emergence of behavior inconsistent with religious values. In this regard, Aqidah Akhlak teachers act as educators, guides, motivators, and supervisors, providing guidance to students on the wise use of social media.